Jezikovno testiranje na tečajih slovenščine kot drugega/tujega jezika - Ferbežar, Ina (Jezik in slovstvo, 1997)
The interest for Slovene as a second/foreign language is on increase. this calls for appropriate language planning, curricular design and related language testing. One of the main objectives of language teaching is linguistic competence, which is evaluated by testing, therefore an exact definition of linguistic competence in need. In recent years the domain of curricular design has been dominated by the communicative approach, which in simplifies terms means simulating real-life language use also in the classroom. In terms of language testing this means designing authentic tests, i.e. tests that will trigger (test) performance typically occurring in non-testing situations. This is also the basis for the work in the project Advancement of Testing Slovene as a Second/Foreign Language, whose objective is to produce various types of tests for various of language knowledge.
Keywords: Slovene; slovenščina; slovenščina kot drugi ali tuji jezik; didactic method; didaktika; metodika; preverjanje znanja